Está en la página 1de 1

Efecta los productos de monomios.

Efecta los productos de monomios.

Efecta los productos de monomios.

1. 3x . 2x =

1. 3x . 2x =

1. 3x . 2x =

2x2

. 3x =

2. 2x2 . 3x =

2. 2x2 . 3x =

3. 5x4 . 4x2 =

3. 5x4 . 4x2 =

3. 5x4 . 4x2 =

4. 8x . 3x5 =

4. 8x . 3x5 =

4. 8x . 3x5 =

5. 2x7 . 4 =

5. 2x7 . 4 =

2.

5.
6.

2x7

.4=

4
2
x . x4
3
5

Efecta los productos de monomios.

6.

4
2
x . x4
3
5

Efecta los productos de monomios.

6.

4
2
x . x4
3
5

Efecta los productos de monomios.

1.

(2x3) (5x3) =

1. (2x3) (5x3) =

1.

(2x3) (5x3) =

2.

(12x3) (4x) =

2. (12x3) (4x) =

2.

(12x3) (4x) =

3.

5 (2x2y3z) =

3. 5 (2x2y3z) =

3.

5 (2x2y3z) =

4.

(5x2y3z) (2y2z2) =

4. (5x2y3z) (2y2z2) =

4.

(5x2y3z) (2y2z2) =

5.

(18x3y2z5) (6x3yz2) =

5. (18x3y2z5) (6x3yz2) =

5.

(18x3y2z5) (6x3yz2) =

6.

(2x3) (5x) (3x2) =

6. (2x3) (5x) (3x2) =

6.

(2x3) (5x) (3x2) =